2007
DOI: 10.1002/pi.2235
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of porous polyacrylamide hydrogels by frontal polymerization

Abstract: Polyacrylamide hydrogels with defined porous structure were synthesized through frontal polymerization (FP) in the presence of NaHCO3 as a foaming agent. Pore properties were analyzed using scanning electron microscopy and mercury intrusion porosimetry. The as‐prepared hydrogels displayed a small cell diameter of ca 2 µm. The dissolved foaming agent dispersing at the level of molecules and the polymerization front propagating step by step should be responsible for the small uniform cell structure. The pore vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 24 publications
1
32
0
1
Order By: Relevance
“…The first direction is to use it to make new types of polymers or existing polymers more easily. For example, FP has been used for the preparation of amphilic gels [69], polymers for controlled release [70], and porous polyacrylamide hydrogels [71].…”
Section: Applicationsmentioning
confidence: 99%
“…The first direction is to use it to make new types of polymers or existing polymers more easily. For example, FP has been used for the preparation of amphilic gels [69], polymers for controlled release [70], and porous polyacrylamide hydrogels [71].…”
Section: Applicationsmentioning
confidence: 99%
“…Washington and Steinbock first demonstrated that FP enables the preparation of homogeneous poly( N ‐isopropylacrylamide) (PNIPAm) hydrogels without compromising their temperature‐dependent property. Ge and colleagues investigated the mechanism of hydrogel preparation by FP in detail and successfully synthesized various hydrogels, such as poly(acrylic acid), polyacrylamide, PNIPAm and so on. Chen and colleagues prepared thermosensitive and pH‐sensitive hydrogels with excellent swelling properties by using such new facile strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The application of PAAm hydrogels in controlled release of agrochemicals and bioactive have been investigated [16,17]. Researchers have been reported porous PAAm hydrogels [18][19][20]. Synthesizing porous hydrogels using solution polymerization method in the presence of porogen (that produce gas bubbles from reaction of porogen with chemicals) is a difficult task, because produced gas bubbles from porogen leave the solution easily.…”
Section: Introductionmentioning
confidence: 99%